THU0235 Adjuvite: A Double-Blind, Randomized, Placebo-Controlled Trial of Adalimumab in Juvenile Idiopathic Arthritis Associated Uveitis. (15th July 2016) - Quartier, P.; Despert, V.; Poignant, S.; Elie, C.; Kone-Paut, I.; Belot, A.; Kodjikian, L.; Monnet, D.; Weber, M.; Bodaghi, B.; Baptiste, A.
Abstract : Background: Juvenile idiopathic arthritis (JIA) patients may develop chronic, anterior uveitis. Topical steroids and methotrexate (MTX) often lack of efficacy. Objectives: To asses safety and efficacty of adalimumab in patients with JIA-associated uveitis. Methods: Elligible patients had chronic, "white eyes" uveitis with inadequate response to topical steroids and MTX, no previous anti-TNF antibody therapy and at least one assessable eye with inflammation quantified by laser flare photometry ≥30 photons/ms. Double-blind randomization at Day 1 (D1) into 2 equal groups, one treated with placebo and one with adalimumab (24 mg/m 2 in patients aged 4 to less than 13 years, 40 mg in patients ≥13), every other week subcutaneous injections. Primary objective: to demonstrate a higher response rate at Month 2 (M2) in the adalimumab arm versus the placebo arm. Response was defined as a 30% reduction of inflammation on laser flare photometry in the eye with the highest flare value at D1 and improvement or a stable appearance on slit lamp examination. From M2 to M12, all patients were allowed to receive adalimumab (open phase) (NCT01385826 ). Results: 34 patients were screened and 31 received at least one injection of study treatment. At M2, in intention-to-treat (Primary objective), there were 9/16 responders in the adalimumab group and 3/15 in the placebo group ( p =0.038, Chi-squared test; RR=2.81, CI95%=[0.94–8.45] with log-binomial model estimation). One patient stopped the trial at D14 (adalimumab group, uveitis worsening) and one at M9 (ocular hypertony). 29 patients reached M12 on adalimumab. There were 5 serious adverse events in 4 patients, all in the placebo group, 4 during the open-label phase, none related to study treatment (investigator assessment). Conclusions: Adalimumab was effective in reducing ocular inflammation within 2 months and well tolerated over 12 months in patients with JIA-associated chronic uveitis and an inadequate response to topical steroids and MTX. Laser flare photometry is a valuable tool to assess early improvement. Disclosure of Interest: P. Quartier Grant/research support from: Abbvie, Novartis, Pfizer, Roche, Consultant for: Abbvie, Novartis, SOBI, Speakers bureau: Abbvie, BMS, Novartis, PfiZer, Roche, SOBI, V. Despert: None declared, S. Poignant: None declared, C. Elie: None declared, I. Kone-Paut Grant/research support from: Roche, SOBI, Consultant for: Abbvie, Chugai, Novartis, Pfizer, Roche, SOBI, A. Belot: None declared, L. Kodjikian Consultant for: Alcom, Alimera, Allergan, Bayer, Bausch&Lomb, Novartis, Thea, Speakers bureau: Alcom, Alimera, Allergan, Bayer, Bausch&Lomb, Novartis, Thea, D. Monnet: None declared, M. Weber: None declared, B. Bodaghi Consultant for: Abbvie, A. Baptiste: None declared